The Correlation Between Nurse Response Time and Service Quality and Family Satisfaction in the Emergency - Didik Wahyudi; Achmad Kusyairi; R. Endro Sulistyono (Health and Technology Journal (HTechJ), 2025)
Response time is a combination of the response time when the patient comes to the health center until he receives service from the staff. The standard time is ≤ 5 minutes for patients to be served after arriving at the emergency room. Long response times can result in the risk of death or disability. Fast and precise response time can create a feeling of satisfaction with the service received. This study aims to determine the correlation between nurse response time, service quality, and family satisfaction in the UPT Kedungjajang Emergency Room Community Health Center. This was multivariate quantitative research using correlational analytical methods with a cross-sectional study. Respondents were obtained in the emergency room of the Kedungjajang Community Health Center, which was held from 26 June to 26 July 2024. The sampling technique used Total Sampling with a sample of 5 nurses and Accidental Sampling with 48 patient families. The instrument uses observation and questionnaires, and it is analyzed using SPSS with the MANOVA test. The research results showed that fast nurse response time at good service quality was 40 respondents (93.0%), fast nurse response time at the satisfaction point was 43 respondents (95.6%), and a significant p-value was obtained at p=0.022 at Nurse Response Time on service quality and p = 0.001 on nurse Response Time on family satisfaction. Service standards in assisting quickly and appropriately are provided to patients in the emergency room by competence and ability. Fast and precise response time can create a feeling of satisfaction with the service received. Nurse training is essential, and health centers are expected to provide triage information boards so that patients and families understand the triage priorities given by nurses.